The Effect of Environmental Corporate Social Responsibility on Furniture Company Brand Trust - Kirana, Larisa Safa; Popy Rufaidah, (Jurnal Manajemen, 2024)
As access to information on environmental issues grows, consumers are increasingly concerned about the impact that companies have on the environment. As a company that has implemented a Corporate Social Responsibility (CSR) program, it needs to pay attention to how its program impacts consumers. Therefore, this study was conducted to investigate how environmental CSR affects brand trust, including feasibility and intentions. The concept of environmental CSR in this study will use three dimensions which are environmental CSR, environmental philanthropy, and environmental customer wellbeing. These dimensions are adopted from previous studies that use environmental CSR as the main focus of the study. Hypothesis testing, validity, and reliability were conducted using PLS-SEM as the analysis methods. The results showed that environmental CSR has a positive and significant effect on brand trust.